Convergence of price dynamics assessed in view of Poland’s accession to the euro area focusing on deflation - Błaszczyk, Paweł; Fojutowski, Łukasz (Wydawnictow Naukowe WNPiD UAM w Poznaniu, 2018)
The primary aim of this study was to assess the degree of Poland’s convergence in terms of price stability, both at the stage of the country’s candidacy to the euro area and in relation to the euro convergence criteria (the so-called Maastricht criteria), and in the broader context of the ECB’s unified monetary policy. The time frame for this study covers the period of 2004–2017. The starting point marks Poland’s accession to the EU, which is a pre-requisite for application to access the euro area. The closing time was chosen due to the availability of data, mainly from the Eurostat database. This was studied in view of the critical analysis of methodology and the method used to establish the Maastricht criterion for the dynamics of the general price level. The methodology of determining the inflation criterion is flawed and not matched to today’s economic conditions, including the definition of price stability applied in the practice of central banking, as well as in the context of the phenomenon of deflation commonly occurring in the last decade. As a consequence, the value of the criterion for a candidate country may turn out to be very low, and may unjustifiably increase the costs of accession to the euro area, also in the long-term perspective. Such a problem should be taken into account in the discussion on Poland’s accession to the euro area, which is usually of a political, as well as social and economic nature. This economic aspect, however, should be key in practice.

Podstawowym celem opracowania jest ocena stopnia konwergencji Polski w zakresie stabilności cen, zarówno na etapie kandydowania do strefy euro i w odniesieniu do kryteriów z Maastricht, jak i w szerszym ujęciu w kontekście jednolitej polityki pieniężnej EBC. Zakres czasowy badania obejmuje okres 2004–2017. Dolna cezura czasowa wynika z przystąpienia Polski do UE, co warunkuje możliwość ubiegania się o przynależność do strefy euro. Górna cezura czasowa wynika z dostępności danych, głównie w odniesieniu do Eurostat. Realizacja celu została dokonana na tle analizy krytycznej metodyki i sposobu wyznaczania kryterium z Maastricht dotyczącego dynamiki ogólnego poziomu cen. Metodyka wyznaczania kryterium inflacyjnego jest wadliwa i niedopasowana do współczesnych uwarunkowań gospodarczych, w tym na tle definicji stabilności cen stosowanych w praktyce bankowości centralnej, a także w kontekście zjawiska deflacji powszechnie występującego w ostatniej dekadzie. W konsekwencji wartość kryterium dla kraju kandydującego może okazać się bardzo niska i może w nieuzasadniony sposób zwiększać koszty akcesji do strefy euro, również w długim horyzoncie czasowym. Taki problem powinien być uwzględniany w dyskusji na temat akcesji Polski do strefy euro, która przeważnie ma charakter polityczny i dalej społeczny oraz ekonomiczny. To aspekt ekonomiczny jednak powinien być w praktyce kluczowy.
Ocena konwergencji dynamiki cen w perspektywie akcesji Polski do strefy euro ze szczególnym uwzględnieniem deflacji
Keywords: deflation; economic integration; euro area; monetary policy; price stability; deflacja; integracja gospodarcza; strefa euro; polityka pieniężna; stabilność cen